South American Anurans: Species Diversity and Description Trends Through Time and Space - Vasconcelos, Tiago S. [UNESP]; Silva, Fernando R. da; Santos, Tiago G. dos; Prado, Vitor H. M.; Provete, Diogo B.; Vasconcelos, TS; DaSilva, FR; DosSantos, TG; Prado, VHM; Provete, DB (Springer, 2019)
Amphibians are especially diverse in the Neotropics and have also one of the highest rates of new species description among terrestrial vertebrates. The first systematic synthesis of South American anurans compiled a list of 1644 species, but there have been no update since the last 19 years. Here, we present a descriptive approach for temporal and spatial patterns of anuran species discoveries in South America, emphasizing trending changes in species description rates and number of researchers authoring a given species description. We recovered 2623 anuran species described in South America between 1758 and mid-2017 from 163 genera and 24 families. There is a high rate of species discovery across time, with at least 10 new descriptions per year in the period examined. Time span to reach multiples of 500 new species has dramatically decreased over time. For instance, it took more than two centuries for the description of 500 species since the first species (1750s), whereas it took about 10-12 years in order to add 500 new anuran species after 1990. Then, the curve of the cumulative anuran species description in South America is far from reaching an asymptote, yet it actually exhibits an exponential shape. Similar historical increase was recorded for the number of authors in papers over time, since descriptions are more collaborative in the last decades. Two major hotspots for new species discovery are depicted herein: (i) the Central and Northern Andes and the adjacent western Amazon (notedly in Ecuador, Peru, and Western Brazil) and (ii) the complex of Brazilian highlands encompassing the Atlantic and Brazilian plateau mountains. These trends are discussed according to singular historical events (including changes in research approaches) and possible explanations for the geographic pattern in species discovery.
Keywords: Species discovery; Neotropical anurans; Anuran list; Description rates; Scientometric analysis; Spatiotemporal trends